2015
DOI: 10.1123/jsep.2014-0212
|View full text |Cite
|
Sign up to set email alerts
|

Affective and Enjoyment Responses to High-Intensity Interval Training in Overweight-to-Obese and Insufficiently Active Adults

Abstract: High-intensity interval training (HIIT) has many known physiological benefits, but research investigating the psychological aspects of this training is limited. The purpose of the current study is to investigate the affective and enjoyment responses to continuous and high-intensity interval exercise sessions. Twenty overweight-to-obese, insufficiently active adults completed four counterbalanced trials: a 20-min trial of heavy continuous exercise and three 24-min HIIT trials that used 30-s, 60-s, and 120-s int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
139
6
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 38 publications
20
139
6
5
Order By: Relevance
“…With this in mind, there may be a minimum exercise duration required to expend adequate energy to achieve weight loss and it is important to find ways to increase the psychological tolerability of these programs, as we have done. Our data complement previous findings demonstrating that reduced-duration sprint bouts elicit more positive affective responses (Martinez et al 2015). For example, Martinez and colleagues (2015) found that affect remained more positive throughout shorter sprint bouts when SIT sessions maintained the same work to rest ratio (1:1) but varied only in sprint duration (30, 60, and 120 s).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…With this in mind, there may be a minimum exercise duration required to expend adequate energy to achieve weight loss and it is important to find ways to increase the psychological tolerability of these programs, as we have done. Our data complement previous findings demonstrating that reduced-duration sprint bouts elicit more positive affective responses (Martinez et al 2015). For example, Martinez and colleagues (2015) found that affect remained more positive throughout shorter sprint bouts when SIT sessions maintained the same work to rest ratio (1:1) but varied only in sprint duration (30, 60, and 120 s).…”
Section: Discussionsupporting
confidence: 69%
“…Considering traditional SIT is already highly demanding (Biddle and Batterham 2015), the practicality of longer sprints as utilized in the Martinez et al (2015) study is questionable and our results are potentially more meaningful to the general population. In our companion paper we demonstrate greater energy expenditure during reduced-duration SIT (5 and 15 s) compared with traditional SIT (Islam et al 2017) and we show here that both of our shorter duration SIT protocols resulted in near pre-exercise affect levels at 30 min postexercise and were evaluated as more enjoyable at 30 min postexercise.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Only 4HIIT increased VO 2 max after 6-week intervention, probably due to a longer tVO 2 max and improved estimated stroke volume. However, a shorter duration of the peak workload duration may lessen perceived exertion for individuals with a low aerobic fitness [14][15][16] and may easily be sustained and be performed with more repetitions, resulting in a similar tVO 2 max. 16 Matsuo et al 17,18 has proposed 3 × 3 min HIIT as a suitable protocol for Japanese as shown in his excellent review of HIIT studies among patients with obesity and metabolic syndrome.…”
Section: Hiit Protocolsmentioning
confidence: 99%
“…Also, physical inactivity is related to high costs with public health [2] therefore, regular exercise seems to be critical for individual and public health. In this context, it has been hypothesized that the affective response (pleasure and displeasure) may be a determinant of behavior [3], based on this premise, several original studies were performed during the last years as an attempt to establish a relationship between aerobic exercise and affective responses [4][5][6][7]. In general, the scientific literature demonstrates that aerobic exercise performed at high intensities is related to negative affective responses [8,9].…”
mentioning
confidence: 99%